Adsorption of Heavy Metal Ions Copper, Cadmium and Nickel by Microcystis aeruginosa. Issue 1 (May 2021) - Zeng, Guoming; He, Sijie; Wu, Jinliang; Sun, Da; Lin, Mengyi; Fu, Xixian; Tang, Longqing; He, Yu
Abstract: In this study, the average removal rate of cadmium, copper and nickel ions was used as the response value. The initial concentration of heavy metal, culture temperature and initial pH were used as the influencing factors. The response surface experiment was carried out by Box-Benhnken's central combination design. Based on this, a quadratic regression equation prediction model was established, and the optimal process conditions for the treatment of three heavy metal ions by Microcystis aeruginosa were obtained. Based on the above experimental results, under the optimal conditions for the removal of three metal ions by Microcystis aeruginosa, scanning electron microscopy (SEM) was used to obtain the changes of surface morphology of algal cells before and after removal of heavy metals by algae cells; fourier infrared was used. Combined with the above physical and chemical indicators, the adsorption kinetics model was used to comprehensively analyze and infer the mechanism of treatment of heavy metal ions by Microcystis aeruginosa, and the actual metal wastewater was collected to verify.